设\(\xi_1,\xi_2,\cdots ,\xi_{n-r}\)是齐次线性方程组\(AX=0\)的基础解系,令
\begin{equation*}
\begin{array}{c}
B_{11}=(\xi_1,0,\cdots ,0),B_{12}=(0,\xi_1,0,\cdots ,0),\cdots ,B_{1n}=(0,\cdots ,0,\xi_1),\\
B_{21}=(\xi_2,0,\cdots ,0),B_{22}=(0,\xi_2,0,\cdots ,0),\cdots ,B_{1n}=(0,\cdots ,0,\xi_2),\\
\cdots\cdots\cdots\cdots\cdots\cdots\cdots\cdots\cdots\cdots\cdots\\
B_{n-r,1}=(\xi_{n-r},0,\cdots ,0),B_{n-r,2}=(0,\xi_{n-r},0,\cdots ,0),\cdots ,B_{n-r,n}=(0,\cdots ,0,\xi_{n-r}),
\end{array}
\end{equation*}
则\(AB_{ij}=0,\forall 1\leq i\leq n-r,1\leq j\leq n\),即\(B_{ij}\in U\)。假设\(\sum\limits_{i=1}^{n-r}\sum\limits_{j=1}^n k_{ij}B_{ij}=0\),即
\begin{equation*}
(\sum\limits_{i=1}^{n-r} k_{i1}\xi_i,\sum\limits_{i=1}^{n-r} k_{i2}\xi_i,\cdots ,\sum\limits_{i=1}^{n-r} k_{in}\xi_i)=0,
\end{equation*}
则
\begin{equation*}
\sum\limits_{i=1}^{n-r} k_{i1}\xi_i=\sum\limits_{i=1}^{n-r} k_{i2}\xi_i=\cdots =\sum\limits_{i=1}^{n-r} k_{in}\xi_i=0.
\end{equation*}
由\(\xi_1,\xi_2,\cdots ,\xi_{n-r}\)线性无关知\(k_{ij}=0,\forall 1\leq i\leq n-r,1\leq j\leq n\)。因此
\begin{equation*}
B_{11},B_{12},\cdots ,B_{1n},B_{21},B_{22},\cdots ,B_{2n},\cdots ,B_{n-r,1},B_{n-r,2},\cdots ,B_{n-r,n}
\end{equation*}
线性无关。对任意\(B\in U\),设\(B=(\beta_1,\beta_2,\cdots ,\beta_n)\),由\(AB=0\)知
\begin{equation*}
A\beta_j=0,\ \forall 1\leq j\leq n,
\end{equation*}
即\(\forall 1\leq j\leq n,\ \beta_j\)是齐次线性方程组\(AX=0\)的解,故存在\(a_{ij}\in\mathbb{F}\),使得\(\beta_j=\sum\limits_{i=1}^{n-r} a_{ij}\xi_i\)。于是,
\begin{equation*}
B=(\sum\limits_{i=1}^{n-r} a_{i1}\xi_i,\sum\limits_{i=1}^{n-r} a_{i2}\xi_i,\cdots ,\sum\limits_{i=1}^{n-r} a_{in}\xi_i)=\sum\limits_{i=1}^{n-r}\sum\limits_{j=1}^n a_{ij}B_{ij},
\end{equation*}
即\(B\)可由\(B_{11},B_{12},\cdots ,B_{1n},B_{21},B_{22},\cdots ,B_{2n},\cdots ,B_{n-r,1},B_{n-r,2},\cdots ,B_{n-r,n}\)线性表出。因此\(B_{11},B_{12},\cdots ,B_{1n},B_{21},B_{22},\cdots ,B_{2n},\cdots ,B_{n-r,1},B_{n-r,2},\cdots ,B_{n-r,n}\)是\(U\)的一个基,\(\dim U=n(n-r)\)。